Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð¸Ð½ÐºÑƒÐ±Ð°Ñ†Ð¸Ð¸ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ð² Ð³Ð¸Ð¿ÐµÑ€Ñ‚Ð¾Ð½Ð¸Ñ‡ÐµÑÐºÐ¸Ñ… Ð½ÐµÑÐ»ÐµÐºÑ‚Ñ€Ð¾Ð»Ð¸Ñ‚Ð½Ñ‹Ñ… ÑÑ€ÐµÐ´Ð°Ñ… Ð½Ð° Ð¸Ñ… Ð¾ÑÐ¼Ð¾Ñ‚Ð¸Ñ‡ÐµÑÐºÑƒÑŽ ÑƒÑÑ‚Ð¾Ð¹Ñ‡Ð¸Ð²Ð¾ÑÑ‚ÑŒ - Nipot, E. E.; Melikhova, S. V.; Bondarenko, V. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
Partial K+ loss by cell as a result of hypertonic incubation into 0.8-1.4 M sucrose solution has been established as contributing to an increase in erythrocyte osmotic resistance to hypotonic shock (50 mM NaCl solution). Cell sensitivity to a change in medium osmotic parameters after dehydration in valinomycine-containing non-electrolyte solutions (1mM final concentration) depends on a temperature of hypertonic incubation.